A simple, cost effective and novel method of establishment of seeds of wild species and interspecific crosses of niger: SIMPLE, COST EFFECTIVE NOVEL METHOD OF ESTABLISHMENT OF WILD SPECIES OF NIGER - M SUJATHA; H D PUSHPA (Journal of Oilseeds Research, 2023)
In niger, seeds of wild species are smaller than cultivated niger but, flowers of Guizotia scabra are large with more number of ray and disc florets. Seeds of wild species planted directly in the field often fail to establish and plantlet recovery is very low. To overcome these limitations, seeds are planted in different containers with various kinds of potting mixes. A simple method has been developed for raising the wild species of niger using peat pellets. Using this procedure, there was 100% germination as well as 100% plant establishment was observed. This procedure can be successfully be used for all the crops with such difficulties in initial establishment of the plants.